A stochastic model for density-dependent microwave Snow- and Graupel scattering coefficients of the NOAA JCSDA community radiative transfer model. (May 2018) - Stegmann, Patrick G.; Tang, Guanglin; Yang, Ping; Johnson, Benjamin T.
Highlights: A bicontinuous random medium model is developed for snow and graupel scattering particles. Single scattering properties of snow and graupel in the microwave regime are calculated using the numerically exact FDTD scheme. Bulk scattering properties and Legendre expansion coefficients for usage in the Community Radiative Transfer Model are derived. Deficiencies and corrections of and for the microwave cloud scattering coefficients of the Community Radiative Transfer Model are explained. Abstract: A structural model is developed for the single-scattering properties of snow and graupel particles with a strongly heterogeneous morphology and an arbitrary variable mass density. This effort is aimed to provide a mechanism to consider particle mass density variation in the microwave scattering coefficients implemented in the Community Radiative Transfer Model (CRTM). The stochastic model applies a bicontinuous random medium algorithm to a simple base shape and uses the Finite-Difference-Time-Domain (FDTD) method to compute the single-scattering properties of the resulting complex morphology.